A Jurisdição na Democracia Constitucional: (im)possibilidades da limitação do poder político em caso de impeachment, São Leopoldo - RS - Müller, Fabiano (Universidade do Vale do Rio dos Sinos, 2016)
In 2016 there was the second process of impeachment under the auspices of the Constitution of the Federative Republic of Brazil of 1988, in effect. Again, this process, which blossoms passions and divides the country into factions, causes controversy when it intends the relation between the political power and a normativity of the Constitution. This issue becomes more complicated because the judgment occurs in a political court that will often decide by policy arguments without following to an imputation of the legal criteria for the configuration of the crime of responsibility. Given this context, it is asked whether it is possible for the Constitutional Jurisdiction to limit the performance of political power in the processes of impeachment? It seeks, therefore, to reconstruct a function of the impeachment institute within the new paradigm of contemporary constitutionalism, where the epicenter of the conduction of democracy occurs through the Constitution, which links the performance of all state actors. In order to carry out a research, Habermas-Streck was used as theoretical reference, in the construction of the Critique of Hermeneutics of Law, making use of the phenomenological-hermeneutic methodology. The theoretical frameworks used have the common ground to evaluate the dangers of the jurisdiction and do not correspond with an inert action of violations of the democratic procedure, establishing armored spaces to the legal action. Thus, as a final result, it is noted that the Judiciary is responsible for intervention in the process of impeachment when there are violations of a constitutional nature, such as the absence of the legal requirement, a broad defense, fulfilling a major function of the larger normative document, which is a limitation of abuses of power.
Keywords: Impeachment; Presidencialismo; Jurisdição constitucional; Poder político; Impeachment; Presidencialism; Constitutional jurisdiction; Political power; ACCNPQ::Ciências Sociais Aplicadas::Direito